2016
DOI: 10.2306/scienceasia1513-1874.2016.42.346
|View full text |Cite
|
Sign up to set email alerts
|

A convergence analysis of the numerical solution of boundary-value problems by using two-dimensional Haar wavelets

Abstract: ABSTRACT:This study provides an analysis of the convergence of the Haar wavelet-based method for solving twodimensional boundary value problems. The convergence analysis shows that the approximation method is of order 2. The analytical results are validated via two numerical examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…The key factors of any numerical method are the accuracy and convergence. These are studied for HWM in [43,45,65]. The convergence theorem is proven in [45], which also shows that the order of convergence of the HWM approach based on [15] is equal to two.…”
Section: Introductionmentioning
confidence: 93%
“…The key factors of any numerical method are the accuracy and convergence. These are studied for HWM in [43,45,65]. The convergence theorem is proven in [45], which also shows that the order of convergence of the HWM approach based on [15] is equal to two.…”
Section: Introductionmentioning
confidence: 93%
“…In the present section, we prove the convergence of the proposed Haar wavelet method. Initially, we introduce some lemmas needed to prove the convergence.Lemma The Haar waveforms and their integral functions are bounded above and their upper bounds are as follows : hifalse(yfalse)1,iandpifalse(yfalse)12j+1,qifalse(yfalse)<()12j+12,fori>1, with =83. Proof Refer [66]. Lemma Let ffalse(ytl+1false)=2vfalse(ytl+1false)y2L2false(normalℝfalse) be a function defined on [ α , β ] at ( l + 1)‐ th time level and ffalse(ytl+1false)i=12M1ai,lhifalse(yfalse) .…”
Section: Convergence Resultsmentioning
confidence: 99%
“…From Wichailukkana et al, 46 it can be observed that the upper bounds of Q i,m (x) satisfy the following:…”
Section: Haar Waveletsmentioning
confidence: 99%